Impact of the Rochester Medical Home Initiative on Primary Care Practices, Quality, Utilization, and Costs. Issue 11 (November 2015) - Rosenthal, Meredith B.; Sinaiko, Anna D.; Eastman, Diana; Chapman, Benjamin; Partridge, Gregory
Abstract : Background: Patient-centered medical homes (PCMH) may improve the quality of primary care while reducing costs and utilization. Early evidence on the effectiveness of PCMH has been mixed. Objectives: We analyze the impact of a PCMH intervention in Rochester NY on costs, utilization, and quality of care. Research Design: A propensity score–matched difference-in-differences analysis of the effect of the PCMH intervention relative to a comparison group of practices. Qualitative interviews with PCMH practice managers on their experiences and challenges with PCMH practice transformation. Subjects: Seven pilot practices and 61 comparison practices (average of 36, 531 and 30, 192 attributed member months per practice, respectively). Interviews with practice leaders at all pilot sites. Measures: Individual HEDIS quality measures of preventive care, diabetes care, and care for coronary artery disease. Utilization measures of hospital use, office visits, imaging and laboratory tests, and prescription drug use. Cost measures are inpatient, prescription drug, and total spending. Results: After 3 years, PCMH practices reported decreased ambulatory care sensitive emergency room visits and use of imaging tests, and increased primary care visits and laboratory tests. Utilization of prescription drugs increased but drug spending decreased. PCMH practices reported increased rates of breast cancer screening and low-density lipid screening for diabetes patients, and decreased rates of any prevention quality indicator. Conclusions: The PCMH model leads to significant changes in patient care, with reductions in some services and increases in others. This study joins a growing body of work that finds no effect of PCMH transformation on total health care spending. Abstract : Supplemental Digital Content is available in the text.